SLA research and language teaching - Ellis, Rod (Oxford University Press, 1997)
The book presents four the main roles of SLA researchers as developing relevant theories, conduting their own classroom research, making research accessible to teachers, and facilitating action research. Each chapter addresses a major issue in the field of SLA and language teaching, for example the teaching of grammar, syllabus design, task evaluation, conciousness-raising, and pragmatic competence